PENGEMBANGAN APLIKASI BUKU AJAR DIGITAL BERBASIS ANDROID PADA MATA KULIAH PENGEMBANGAN BAHAN AJAR PRODI TEKNOLOGI PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Sari Asih; Farida Febriaty; Abd. Haling (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research focused on the Educational Technology Study Program and identifieda problem in learning activities, namely the lack of teaching materials in the form oftextbooks for the Teaching Materials Development course. The purpose of this studywas to determine the teaching materials needs of Educational Technology studentsfor the Teaching Materials Development course and to assess the validity andpracticality of the Android-Based Digital Textbook Application as teaching materialfor the Teaching Materials Development course. The research was conducted usingthe Alessi & Trollip Research & Development model. Data collection was conductedusing observation techniques and questionnaires distributed by respondents andvalidators. The results of the study concluded: (1) Educational Technology studentsneed teaching materials that can then be developed into an Android-Based DigitalTextbook Application; (2) the Android-Based Digital Textbook Application wasdeclared valid and practical by the validators, with scores of 87.5% by mediaexperts, 82.5% by material experts, and 86% by the course lecturers. Overall, theresults were categorized as Good.